Effect of perceived corporate social responsibility on affective commitment and employee work behavior in mining companies in Ghana – evidence from Golden Star Resources - Eklu, Rei Quarshie (University of Mines and Technology, 2021)
Employees are perceived by firms’ CEOs as the key stakeholder applying pressure and giving motivations to socially dependable behavior since a positive perception of CSR affects their emotional, attitudinal and behavioral responses. The study’s main aim is “to evaluate employees’ perceptions of CSR in the Ghanaian mining industry” as well as“examine the effect of the employee perceptions of CSR on their individual commitment and work behavior”, using Golden Star Co. Ltd as a case study. The study is a descriptive survey using the quantitative research approach to collect data with questionnaire from a randomly sampled respondents of 250 employees of Golden Star Resources. The study findings indicated that employees of Golden Star Co. Ltd generally have a positive perception towards all aspects of CSR activities undertaken in the company. The findings showed that employees’ perception of CSR activities of a company has a positive significant effect on organisational citizenship behaviour (OCB).Particularly, OCB was significantly impacted the strongest by their perception of CSR activities towards the environment, followed by their “perception of CSR towards employees”. Employees’ CSR perception of activities towards the society and customers did not have significant impact on their OCB. The findings also showed that a company’s CSR activities influences employees’ feelings towards their organisation (affective organisational commitment, AOC), which further affects their willingness to perform constructive behaviour for their organisation (OCB). Thus, statistically, there is a “full mediating effect of AOC between perceived CSR and OCB”. It is recommended that mining companies in Ghana give particular attention to the natural environment and employees in their CSR activities since these have the most significant impact on their affective commitment and corporate behaviour
ii,104p:,ill.
Keywords: Corporate social responsibility; Organizational behaviour; Industrial relationships; Mining industry